GOGOLIVSCIY CILIA AND BOUN (BOUNYAC, BOUNO) MANGY AS UKRAINIAN AREY - MARS - Pushyk, S. G. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In research new looks are offered on folk-lore-mythological bases not only Gogolivsky Eye-lash but also other appearances, localities and temples, heathen ceremonies and others like that.